THE ETHICAL CLIMATE AND EMPLOYEE PERFORMANCE IN PRIVATE SPORTS SCHOOLS: ENHANCING BUSINESS SUCCESS - Akhmad Niko Apriadi; Annisa Nur Fitriani; Asep Suprianto (Journal of Business Administration, 2022)
The study aimed to investigate the relationship between the ethical climate and employee performance in private sports schools. The method used is explanatory, where data is obtained through questionnaires filled out by employees in three private sports schools in Bandung City. The questionnaire measures employees' perceptions of the ethical climate in the workplace and evaluates their performance. Simple regression inferential statistical analysis is used to analyze the collected data. The results showed a positive relationship between a strong ethical climate and employee performance. In the context of private sports schools, employees who perceive a positive ethical climate tend to perform better. These findings emphasize the importance of establishing and maintaining a healthy ethical climate in the work environment, as well as providing encouragement for school management to adopt management practices that support ethical integrity and commitment. This research contributes to the understanding of the relationship between ethical climate and employee performance, as well as practical implications for the management of private sports schools.